To equal 24 using the numbers 1, 1, 9, and 6, you can use the following mathematical expression: (9 - 1) x (6 + 1) = 8 x 7 = 56. Then, take the square root of 56 to get 24.
A possibility is: (8-3-1) times 6 = 24
6(5 - 7/7) = 6(5 - 1) = 6 x 4 = 24
6(7 - (2 + 1)) = 24 2 plus 1 equals 3. 7 minus 3 equals 4. 4 times 6 equals 24.
One possibility is: 2*(8-6)*6 = 24
It is: 6*(5-2)+6 = 24.
A possibility is: (8-3-1) times 6 = 24
It can be done by: (9-5) times 6 times 1 = 24
(1+4)x 6-6= 24
96 x 1/4 = 24
2*(6/6 + 11) = 2*(1 + 11) = 2*12 = 24. Simple!
6(5 - 7/7) = 6(5 - 1) = 6 x 4 = 24
6(7 - (2 + 1)) = 24 2 plus 1 equals 3. 7 minus 3 equals 4. 4 times 6 equals 24.
One possibility is: 2*(8-6)*6 = 24
It is: 6*(5-2)+6 = 24.
To make 24 using 3, 4, 5, and 6, you can use the following mathematical expression: (5 x 4) + (6 ÷ 3) = 20 + 2 = 24. This equation utilizes multiplication and division to combine the numbers in a way that results in the target number of 24.
6 * [5-(2-1)] = 6*[5-1] = 6*4 = 24
To make 6 6 2 9 equal 24, you can use the following equation: 6 ÷ (1 - (2 ÷ 9)) = 24. This equation involves using the division operation and parentheses to manipulate the numbers in a specific order to achieve the desired result of 24.